LITERATURE REVIEW OF NEPHROTIC EDEMA MANAGEMENT: A Literature Review - Pramuti, Agysza Ulfiantika; Estu Pratiwi, Prasetyaning (Faculty of Medical - UPN Veteran Jawa Timur, 2025)
Abstract Background. Nephrotic syndrome (NS) is a renal disorder characterized by proteinuria, hypoalbuminemia, hyperlipidemia, and edema. Among these, edema remains a prominent clinical manifestation affecting patient quality of life and signaling disease progression. Understanding its multifactorial pathophysiology is essential for optimizing treatment strategies. Methods. A systematic review of peer-reviewed literature from 2020 to 2024 was conducted using PubMed, ScienceDirect, and Elsevier. Search terms included